Molecular mechanisms of ferroptosis and the potential therapeutic targets of ferroptosis signaling pathways for glioblastoma - Zhang, Meng; Lei, Qian; Huang, Xiaobo; Wang, Yi (Frontiers in Pharmacology, 2022)
Ferroptosis is a newly identified form of cell death that differs from autophagy, apoptosis and necrosis, and its molecular characteristics include iron-dependent lipid reactive oxygen species accumulation, mitochondrial morphology changes, and membrane permeability damage. These characteristics are closely related to various human diseases, especially tumors of the nervous system. Glioblastoma is the most common primary malignant tumor of the adult central nervous system, and the 5-year survival rate is only 4%–5%. This study reviewed the role and mechanism of ferroptosis in glioblastoma and the research status and progress on ferroptosis as a potential therapeutic target. The mechanism of ferroptosis is related to the intracellular iron metabolism level, lipid peroxide content and glutathione peroxidase 4 activity. It is worth exploring how ferroptosis can be applied in disease treatment; however, the relation between ferroptosis and other apoptosis methods is poorly understood and methods of applying ferroptosis to drug-resistant tumors are insufficient. Ferroptosis is a promising therapeutic target for glioblastoma. In-depth studies of its mechanism of action in glioblastoma and applications for clinical treatment are expected to provide insights for glioblastoma patients.